The Protection and Inheritance of Cuotaiji in Guizhou China and the Integration of Contemporary Drama - Wei, Xu; Reangdet, Manusak; Atipattayakul, Chawalit (RATANABUTH JOURNAL, 2024)
To conserve and prevent loss and it is historical research with actual fieldwork. The research results found that: the development of human civilization, culture is the backbone of a nation and the profound accumulation of national history. How to protect and inherit those precious cultural heritages has become the unshirkable responsibility of the academic community and creators. Cuotaiji, a Yi ethnic group in Guizhou Province, China, is a treasure that was included in the first batch of China’s intangible cultural heritage list in 2006. The application of intangible cultural heritage is to slow down the loss of this culture and take effective protection measures. After field investigation, the author found that the protection, inheritance and promotion of Cuotaiji in Guizhou, China has weak publicity, insufficient popularity and influence, and insufficient investment, which makes it difficult for inheritors and villagers who learn Cuotaiji to survive; the inheritors have outdated inheritance ideas and lack of professional talents to organize and coordinate; in order to solve these problems, the author studied the history and traditional characteristics of Cuotaiji in Guizhou, China, the current situation and innovative methods of protection and inheritance, and the integration with modern drama, and proposed some innovative protection and promotion strategies. First, innovate the costume shape of Cuotaiji, retaining national elements while combining modern materials and aesthetics. Secondly, try to experiment with local characteristics and Mandarin versions in the lines to promote the spread of Cuotaiji. Finally, from the creative level, we will integrate Cuotaiji with modern drama, which will not only protect inheritance but also realize innovative promotion. With an innovative spirit and an open vision, we will contribute to the protection and inheritance of our country’s intangible cultural heritage. Let these cultural treasures shine more brilliantly in the new era.